2019
DOI: 10.1111/febs.14782
|View full text |Cite
|
Sign up to set email alerts
|

Structural, biochemical and biophysical characterization of recombinant human fumarate hydratase

Abstract: Fumarate hydratases (FHs, fumarases) catalyze the reversible conversion of fumarate into l‐malate. FHs are distributed over all organisms and play important roles in energy production, DNA repair and as tumor suppressors. They are very important targets both in the study of human metabolic disorders and as potential therapeutic targets in neglected tropical diseases and tuberculosis. In this study, human FH (HsFH) was characterized by using enzyme kinetics, differential scanning fluorimetry and X‐ray crystallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…It is suggested that TeFum also becomes active at these growth temperatures. The optimum pH for CmFUM (pH 7.5 for fumarate hydration; pH 8.5 for l-malate dehydration) and TeFum (pH 7.0 for fumarate hydration; pH 7.5 for l-malate dehydration) were approximately the same as those of Class ІІ Fums from other organisms (pH 6.5-8.5, seven species: R. oryzae, Synechocystis 6803, Saccharomyces cerevisiae, S. solfataricus, C. glutamicum, A. thaliana, and Homo sapience; Puchegger et al, 1990;Keruchenko et al, 1992;Genda et al, 2006;Song et al, 2011;Zubimendi et al, 2018;Ajalla Aleixo et al, 2019;Katayama et al, 2019; Figures 2B,D). Intercellular pH of C. merolae and cyanobacteria is maintained near neutral where CmFUM and TeFum show enzymatic activities (Coleman and Colman, 1981;Zenvirth et al, 1985;Mangan et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…It is suggested that TeFum also becomes active at these growth temperatures. The optimum pH for CmFUM (pH 7.5 for fumarate hydration; pH 8.5 for l-malate dehydration) and TeFum (pH 7.0 for fumarate hydration; pH 7.5 for l-malate dehydration) were approximately the same as those of Class ІІ Fums from other organisms (pH 6.5-8.5, seven species: R. oryzae, Synechocystis 6803, Saccharomyces cerevisiae, S. solfataricus, C. glutamicum, A. thaliana, and Homo sapience; Puchegger et al, 1990;Keruchenko et al, 1992;Genda et al, 2006;Song et al, 2011;Zubimendi et al, 2018;Ajalla Aleixo et al, 2019;Katayama et al, 2019; Figures 2B,D). Intercellular pH of C. merolae and cyanobacteria is maintained near neutral where CmFUM and TeFum show enzymatic activities (Coleman and Colman, 1981;Zenvirth et al, 1985;Mangan et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…The K m of CmFUM (0.27 mM) and TeFum (0.14 mM) for fumarate were within the range of most Class ІІ enzymes (0.03-3.07 mM, nine species: E. coli, C. glutamicum, R. oryzae, Synechocystis 6803, S. cerevisiae, S. solfataricus, A. thaliana, T. thermophilus, and H. sapience;Woods et al, 1988;Puchegger et al, 1990;Keruchenko et al, 1992;Mizobata et al, 1998;Song et al, 2011;Lin et al, 2018;Zubimendi et al, 2018;Ajalla Aleixo et al, 2019; A B…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…We do not consider Site B due to the unknown and conflicting evidence surrounding its importance. For this study we chose to focus on the crystal structure 5upp 24 , which covers residues 49-510 of the 510 residue protein assembled into a homotetramer.…”
Section: Resultsmentioning
confidence: 99%